KONSEP DIRI REMAJA DALAM PERNIKAHAN DINI DI KOTA PEKANBARU - Wan Vabella Adrilianza; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
In the modern age, the phenomenon of marriage at a young age is still common in the community. Early marriage is not new in Indonesia. Early marriage or underage marriage, means getting married in a state that is still not financially secure, and is usually still a student or student status. Early marriage not only has a negative side but also has a positive side. Law Number 16 Year 2019 stipulates the age of 19 years as the adult age of a woman and 19 years of age for a man to get married. The purpose of this study was to see how teenage self-concept in early marriage in Pekanbaru City.This type of research is qualitative with a phenomenological approach. Data collection techniques through observation, in-depth interviews and documentation. Research subjects were four teenagers in early marriage in Pekanbaru City. The validity of the data from this study is the extension of participation and triangulation.The results of this study indicate that the physical aspects of adolescents who engage in early marriage are seen from their own views as physical humans, family environment, friendship, and community views about the physical informants. Based on self-views, two informants had positive physical aspects and two informants had negative physical aspects. Whereas physical views based on others, one informant has positive physical aspects and three negative aspects. Psychological aspects of adolescents who do early marriage can be seen from the personality and acceptance of the conditions as a person who does early marriage. Two research informants assessed his personality and acceptance of his condition positively and two research informants assessed his personality and condition acceptance negatively. The social aspects of adolescents who engage in early marriage can be seen from its interactions with the family, friendship, community. Two informants have negative social aspects in interacting with family, two informants have positive social aspects in the family. All informants have positive social aspects in the friendship environment, two informants have negative social aspects in the community environment, two informants have positive social aspects in the community. Keywords:Teenage, Sel Concep, Physical Aspects, Psychological Aspects, Social Aspects